Physical and topical structures of manpower discourse: a contrastive rhetoric analysis in Southeast Asia - Edward Jay Mansarate Quinto (Penerbit UKM, 2015)
This paper explores the physical and topical structures of thirty paragraphs culled from websites of Philippine, Indonesian and Malaysian manpower agencies. Drawing on the frameworks of Simpson (2000) and Lautamatti (1987), the study describes potential regional (Southeast Asian) and national preferences of writers on a subgenre of L2 professional writing, called manpower discourse (MD). The physical structure analysis points to slight but statistically insignificant differences between the data sets. Such analysis aids in the description of a possible regional preference in the physical structure of MD in Southeast Asia, which appeals to directness and simplicity. The topical structure analysis (TSA) shows that there is a stronger demand for internal coherence in Philippine MD, compared with Indonesian MD and Malaysian MD. Specifically, the analysis reveals that topical development is more sophisticated in Philippine MD attributed to the use of some form of topical reoccurrence and some kind of topical progressions in all paragraphs, which was not observed in the internal structure of paragraphs from Indonesian and Malaysian MD. Moreover, Philippine MD seems to keep up with one valued characteristic of composition in English: to develop ideas using sequential and extended parallel progressions. Also, topical depth is found to be most elaborate in Philippine MD than in the Indonesian and Malaysian counterparts. The paper closes with a discussion of implications for professional writing, specific to manpower discourse and teaching writing coherence based on socially and culturally relevant inputs.